Peningkatan Hasil Belajar IPA pada Materi Sumber Daya Alam dengan Menetapkan Model Pembelajaran Example Non Example - Ramdhan Witarsa; Nurmalina Nurmalina; Musmulyadi Musmulyadi (Departement of Mathematics Education, 2022)
This research originates from the fact that many grade IV elementary school students have difficulty understanding natural resources material. This is because the teacher does not provide learning natural resources in accordance with the students' concrete situations. One solution to overcome this problem is to use the Example Non-Example model. Example Non-Example is a learning model that is oriented to everyday experiences. Thus, the purpose of this study was to describe the increase in class IV student learning outcomes in natural resource material using the Example Non-Example model. This study uses a qualitative and quantitative approach to the form of research, namely classroom action research. This research was conducted in two cycles and each cycle held 2 meetings. This research was conducted at SD Negeri 013 Rambah with the research subject being class IV SD. Collecting data in this study using documentation, observation, tests, and questionnaires. Data were analyzed using qualitative and quantitative data analysis. The increase in student learning outcomes in learning natural resources with the Example Non-Example model in each cycle can be seen from the average score of 73.3 with an 80% completeness percentage in cycle I and an average score of 80.5 with a 92% completeness percentage in cycle II. So, learning with the Example Non-Example model in natural resource science subjects can improve the learning outcomes of fourth grade students at SD Negeri 013 Rambah.